Effect of Different Intensity Exercise on Intestinal Microbiota - ÖZKAN, Ali; DEMİRHAN, Bilal; genç, Ayça; AYDIN, Recep; ERKILIÇ, Ali Ozan; GÜDER, Ferhat; MÜLHİM, Mustafa Alper (Progress in Nutrition, 2021)
Aim: The aim of this study is to investigate the effect of different intensity exercise on the intestinal microbiota. Material and Method: Professional footballers (n = 5), amateur footballers (n = 5) and sedentary ones (n = 5), a total of 15 volunteer men whose age were between 18-24 participated in the study. In order to determine the Pielou's Evenness Index of all groups, metagenomics analysis was performed using the Next Generation Sequencing method with Illumina MiSeq analyzer by taking stool sample for once. In addition, Food frequency questionnaire was applied to determine participants’ eating habits. SPSS 20.0 and Minitab 17 package programs were used in statistical analysis, and the significance level was taken as p